Prediction of Short-Time Rainfall Based on Deep Learning. (31st March 2021) - Sun, Dechao; Wu, Jiali; Huang, Hong; Wang, Renfang; Liang, Feng; Xinhua, Hong
Abstract : Short-time heavy rainfall is a kind of sudden strong and heavy precipitation weather, which seriously threatens people's life and property safety. Accurate precipitation nowcasting is of great significance for the government to make disaster prevention and mitigation decisions in time. In order to make high-resolution forecasts of regional rainfall, this paper proposes a convolutional 3D GRU (Conv3D-GRU) model to predict the future rainfall intensity over a relatively short period of time from the machine learning perspective. Firstly, the spatial features of radar echo maps with different heights are extracted by 3D convolution, and then, the radar echo maps on time series are coded and decoded by using GRU. Finally, the trained model is used to predict the radar echo maps in the next 1-2 hours. The experimental results show that the algorithm can effectively extract the temporal and spatial features of radar echo maps, reduce the error between the predicted value and the real value of rainfall, and improve the accuracy of short-term rainfall prediction.